Exploring Critical Success Factors of Education for Sustainable Development (ESD) in Malaysia - Amina Suleiman Mohamoud; Siti Noorsuriani Maon; Erne Suzila Kassim (Journal of International Business, Economics and Entrepreneurship)
This study seeks to explore the critical success factors of education for sustainable development. As the world has realized a move towards sustainability is inevitable, sustainable development (SD) was adopted and headed by the United Nations. To embed the concept of sustainable development in the minds of young people who will be the future generations and to create the best practice and attitude towards environment, education for sustainable development (ESD) was introduced as an approach of teaching and learning in schools. Malaysia has implemented (ESD) and became a member of the Foundation of Environmental Education (FEE) and a member of the Worldwide Fund for Nature (WWF) which is running the eco school program nationally. However, as the uptake of the ecoschool status and environmental excellence of ‘Green Flag’ is very low, this gives the hint of the need for these schools to be aware of the success factors which can lead to effective implementation of education for sustainable development. Hence, an exploratory study based on the grounded theory approach was conducted. The data was attained from interviews with eco leaders of awarded eco-schools and with a “program officer” of the eco-school program in WWF Malaysia. The findings suggest for a model that consists of 33 critical success factors of implementing (ESD), fulfilled through four main elements of 1) the eco- committee, 2) the teacher (eco leader), 3) the students and 4) the school management. This model can be used as guidelines for those seeking to effectively implement education for sustainable development in eco-schools. The findings also emphasize on the importance of cooperation and collaboration between the school community, the public and private agencies, and non-government agencies to fulfill the sustainable development goals.